The role of offshore financial centers in the process of renminbi internationalization - Yin-Wong Cheung (Asian Development Bank Institute (ADBI), 2014)
The People's Republic of China (PRC) has been quite aggressive recently in promoting the international use of its currency, the renminbi. Historical experience suggests that an active offshore market is essential for a global currency. Indeed, anecdotal evidence affirms the role of offshore markets in pushing the renminbi currency to the world. One should not, however, overplay the contribution of offshore markets. While offshore markets offer the opportunities to experiment with the global use of the currency, the overseas acceptance of the renminbi is ultimately determined by both internal and external economic forces, and geopolitical factors. With its relatively small size, the offshore renminbi is not likely to pressure the PRC and alter its financial liberalization policy. A well-organized offshore renminbi market will complement the PRC's renminbi internationalization policy, but it is not possible to raise the currency's global status beyond the level justified by its economic and political attributes.
Keywords: F33; 330; renminbi; yuan; international monetary policy; currency internationalization; offshore currency market; onshore currency market; foreign exchange; financial centers